2002
DOI: 10.1523/jneurosci.22-23-10192.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Morphine Treatment Inhibits Opioid Receptor Desensitization and Internalization

Abstract: Chronic opioid receptor (OR) activation by morphine causes distinct cellular adaptations responsible for the development of tolerance. The present study examines the effect of chronic morphine exposure on the ability of high-efficacy agonists to mediate ␦-OR (DOR) and -OR (MOR) uncoupling and internalization, two regulatory mechanisms contributing to rapid desensitization of OR function. Chronic morphine treatment (1 M; 72 hr) of DOR carrying neuroblastoma x glioma (NG108-15) hybrid cells, a prototypical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 40 publications
6
60
0
1
Order By: Relevance
“…ARRB1 regulates the desensitization of numerous GPCRs including OPRM1, D1 and D2 dopamine receptors and emerging evidence has demonstrated that ARRB1 functions as a scaffold protein that links GPCRs to intracellular signaling, such as MAPK and as a transcription factor that translocates to the nucleus (16,17). A recent study showed that chronic morphine treatment blocked the agonist-induced redistribution of ARRB1 in stably OPRM1-transfected HEK293 cells through the persistent stimulation of MAPK activity and the authors concluded that chronic morphine treatment produces adaptational changes at the ARRB1 level (18). These observations and our findings suggest that the drug response of PBLs to morphine mediates the down-regulation of ARRB1 expression during morphine treatment and reflects the overall cellular response to opioid signaling in an individual.…”
Section: Discussionmentioning
confidence: 99%
“…ARRB1 regulates the desensitization of numerous GPCRs including OPRM1, D1 and D2 dopamine receptors and emerging evidence has demonstrated that ARRB1 functions as a scaffold protein that links GPCRs to intracellular signaling, such as MAPK and as a transcription factor that translocates to the nucleus (16,17). A recent study showed that chronic morphine treatment blocked the agonist-induced redistribution of ARRB1 in stably OPRM1-transfected HEK293 cells through the persistent stimulation of MAPK activity and the authors concluded that chronic morphine treatment produces adaptational changes at the ARRB1 level (18). These observations and our findings suggest that the drug response of PBLs to morphine mediates the down-regulation of ARRB1 expression during morphine treatment and reflects the overall cellular response to opioid signaling in an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, agonist-specific desensitization of ERK signaling pathway has been reported for the OR (Eisinger et al, 2002;Hong et al, 2009). In addition, differential kinetic patterns of ERK activation by individual OR agonists have also been observed (Eisinger and Schulz, 2004;Audet et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…ERK1/2 activated by etorphine is quite transient, whereas ERK1/2 activated by morphine is quite persistent (Eisinger and Schulz, 2004). Moreover, such different patterns of ERK activation induced by morphine and etorphine have been linked to their ability to differently desensitize and internalize OR (Eisinger and Schulz, 2004;Eisinger et al, 2002;Audet et al, 2005). However, the molecular mechanisms underlying this differential regulation of ERK activation by distinct agonists remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study showed that DOR-eGFP internalization is strongly correlated with receptor phosphorylation and uncoupling from G-proteins [38] . Chronic morphine treatment produces adaptive changes at the β-arrestin 1 level, which in turn attenuate the agonist-mediated desensitization and internalization of GPCRs [39] . Patwardhan et al have shown that peripheral activation of primary afferent nociceptors with bradykinin [40] or trypsin [41] enhances both the targeting of DORs to the cell surface and receptor competence.…”
Section: Hypothesis Of the Development Of Morphine Antinociceptive Tomentioning
confidence: 99%